Anterior rehabilitation using 3D-printed dental implants and custom-made immediate restorations through additive manufacturing. - Matos , Jefferson David Melo de; Rodrigues , Michael Frank; Oliveira, Samantha de Almeida Ferreira; Silva , Thiago Baum da; Viaro , Thiago R V; Queiroz , Daher Antonio; Lopes, Guilherme da Rocha Scalzer (Brazilian Journal of Implantology and Health Sciences, 2024)
Dental implants have evolved significantly, but various failures continue to arise, initially focused on osseointegration and, more recently, involving aesthetic concerns. However, the criteria for evaluating aesthetic failures are still not well defined. These failures can be classified into issues related to the white tissue (crowns) and pink tissue (gingiva). This study presents a rehabilitation protocol that uses 3D-printed surgical guides and adaptations for bone and tissue grafts, with a focus on aesthetic restoration. The case of a fractured upper left central incisor illustrates the application of an implant system for immediate rehabilitation, highlighting the effectiveness of immediate implant and restoration techniques in achieving ideal aesthetic and functional outcomes.